Evaluation of n-(n-butyl) thiophosphate triamide (NBPT) treated urea on sweet potato (Ipomoea batatas) growth and yield - Mohd Nasirudin, Muhammad Zulhilmi; Sakimin, Siti Zaharah; Md Jaafar @ Ahmad Jaafar, Noraini; Yusop, Mohd Khanif (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Ipomoea batatas or sweet potato is one of the plants that have earned attention among farmers around 1980, meanwhile, the production has decreased through the years. The production is decreased due to lack of Loss of urea are frequently happened during the heavy rainy season where farmers are unable to control through water sliding, nitrification, denitrification, volatilization, mineralization and immobilization. Cost of production will increase and it will lead to decrease in yield production if the problems are not counter to solve. Thus application of n-(n-butyl) thiophosphate triamide (NBPT) fertilizer acts as a ingredient that slow down the urea decomposition process and minimizes the loss of nitrogen (N) fertilizer. The objective of study was to study the efficacy of urea treated with the urease inhibitor Agrotain® [active ingredient N-(n-butyl) thiophosphate triamide (NBPT)] on growth and yield of sweet potato. The experiment was carried out in Field 15, Faculty of Agriculture, Universiti Putra Malaysia, Serdang, Malaysia. Sweet potato cutting was used and planted on the bed prior subjected to six treatments, two of which were control [T1 = farmers practice (100% urea) and T2 = no fertilizer (0% urea)], and four Agrotain Treated Urea (ATU) treatments [T3 = 60% ATU, T4 = 80% ATU, T5 = 100% ATU applied as similar as T1 (in term of rate and frequency) and T6 = 120% ATU]. The experiment was arranged in Randomized Complete Block Design (RCBD) with 4 replications. The plant was destructively sampled after 4 months of planting for determination of fresh and dry weight of shoot biomass and yield of sweet potato. Data has been analyzed by using Statistical Analysis (SAS 9.4). Result of study shows 80% ATU exhibited the significant and highest growth and yield of sweet potato after 4 months of planting. In conclusion, the application of 80% ATU improved the performance of growth and yield of sweet potato plant and could be recommended to farmer to increase their yield and reduce the fertilizer cost.